Exploring the Prevalence and Determinants of Self-Medication During Pregnancy Among Women from South Punjab, Pakistan - Madiha, Madiha; Jabbar, Sehar; Masood, Imran (UI Scholars Hub, 2025)
Background: For developing countries with high neonatal and maternal mortality rates, any practice that may threaten the maternal-fetal health must be gauged. This study evaluated the prevalence and contributing factors of self-medication during pregnancy among women opting for antenatal or postnatal care in South Punjab, Pakistan. Methods: A cross-sectional study design was used. Data was collected from 424 women, selected through multi-stage sampling, who visited health care facilities located in six randomly selected cities of South Punjab. Outcomes reported by descriptive and inferential statistics (p < 0.05). Binary logistic regression analysis was performed to determine the association of self-medication with different factors. Results: Most of the women were involved in self-medication practice (38.9%) during pregnancy and usually preferred it over visiting a doctor due to the availability of medicines at home (37.6%). Self-use of analgesics, muscle relaxants, and anticoagulants was alarmingly high. Rural background (AOR: 2.060, 95%CI: 1.239–3.425), age group between 21–25 years (AOR: 3.273, 95%CI: 1.141–9.387), and having a history of miscarriage or abortion (AOR: 1.881, 95%CI: 1.080–3.039) were significant predictors. Conclusions: The study revealed that self-medication was common among pregnant women, especially for analgesics, muscle relaxants, and anticoagulants. Rural residence, younger age (21–25 years), and history of miscarriage or abortion were major determinants. This highlights the need for targeted awareness and counselling that may benefit these high-risk groups.